Birth Outcomes for Medically High-Risk Pregnancies: Comparing Group to Individual Prenatal Care - Heberlein, Emily C.; Smith, Jessica C.; LaBoy, Ana; Britt, Jessica; Crockett, Amy (American Journal of Perinatology, 2021)
Objectives Group prenatal care models were initially designed for women with medically low-risk pregnancies, and early outcome data focused on these patient populations. Pregnancy outcome data for women with medically high-risk pregnancies participating in group prenatal care is needed to guide clinical practice. This study compares rates of preterm birth, low birth weight, and neonatal intensive care unit admissions among women with medical risk for poor birth outcomes who receive group versus individual prenatal care.Study Design This retrospective cohort study uses vital statistics data to compare pregnancy outcomes for women from 21 obstetric practices participating in a statewide expansion project of group prenatal care. The study population for this paper included women with pregestational or gestational hypertension, pregestational or gestational diabetes, and high body mass index (BMI > 45 kg/m2). Patients were matched using propensity scoring, and outcomes were compared using logistic regression. Two levels of treatment exposure based on group visit attendance were evaluated for women in group care: any exposure (one or more groups) or minimum threshold (five or more groups).Results Participation in group prenatal care at either treatment exposure level was associated with a lower risk of neonatal intensive care unit (NICU) admissions (10.2 group vs. 13.8% individual care, odds ratio [OR] = 0.708, p < 0.001). Participating in the minimum threshold of groups (five or more sessions) was associated with reduced risk of preterm birth (11.4% group vs. 18.4% individual care, OR = 0.569, p < 0.001) and NICU admissions (8.4% group vs. 15.9% individual care, OR = 0.483, p < 0.001). No differences in birth weight were observed.Conclusion This study provides preliminary evidence that women who have or develop common medical conditions during pregnancy are not at greater risk for preterm birth, low birth weight, or NICU admissions if they participate in group prenatal care. Practices who routinely exclude patients with these conditions from group participation should reconsider increasing inclusivity of their groups.Key Points
Keywords: birth outcomes; CenteringPregnancy; gestational diabetes; gestational hypertension; group prenatal care; low birth weight; outpatient obstetrics; preterm birth; prenatal care